Pendampingan Penyusunan Perangkat Pembelajaran Berbasis Problem Based Learning untuk Meningkatkan Komunikasi Matematika Siswa: Assistance in the Preparation of Problem-Based Learning Tools to Improve Students' Mathematical Communication - Setyaningsih, Nining; Khotimah, Rita Pramujiyanti; Jannati, Arum Afdhalishani; Davi, Dian Rahmawati (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
This community service activity aims to assist mathematics teachers in the preparation of Problem Based Learning (PBL)-based learning tools and implementation in order to improve students' mathematics communication at SMP Muhammadiyah Surakarta Special Program. PBL is a learning model that emphasizes the solving of real problems and the use of mathematics in everyday contexts. This activity began with the identification of problems in the mathematics learning process at SMP Muhammadiyah Surakarta Special Program. The team provided assistance to mathematics teachers in designing the preparation of RPP and LKPD. After the learning tools have been compiled, then a discussion that examines the learning tools is produced. This community service activity has an impact on improving students' mathematics communication at SMP Muhammadiyah through a PBL-based learning approach. By applying relevant learning tools and involving students in solving real problems, there is an increase in mathematics communication of students of SMP Muhammadiyah PK Surakarta.